Library Support: Implications on Student Well-being (British Journal of Multidisciplinary and Advanced Studies, 2024)
Fostering healthy, supportive contexts that holistically enrich growth is fundamental to the central mission of educational institutions. This study evaluated how college students perceive library support across various dimensions and its influence on their well-being, involving 303 students from a private institution in Cagayan de Oro City, Philippines. Utilizing a researcher-made questionnaire and focus group discussions, it explored the relationship between library support and student well-being. The study revealed that the participants' assessment of library support across physical, intellectual, social, and environmental dimensions was generally high, reflecting satisfaction with resources, assistance, social environments, and the library's ambiance. They also reported high well-being levels in physical, cognitive, and social aspects, indicating a positive overall self-assessment. The participants' library support assessment significantly influenced their well-being levels, suggesting that high-quality library support contributes to higher well-being. Key themes from the students' library support experiences included a conducive environment, technological support, collaboration opportunities, and distractions. This study emphasizes the significant role of academic libraries in enhancing student well-being, advocating for comprehensive library services and a holistic approach to student welfare in higher education. It points to institutions to provide welcoming and collaborative library spaces by applying a "therapeutic landscape" ethos across education, and conducting further research on the influence of library support on well-being across different contexts.